PERCEIVED ORGANIZATIONAL SUPPORT, PSYCHOLOGICAL EMPOWERMENT, AND JOB PERFORMANCE: MEDIATING ROLE OF ORGANIZATIONAL JUSTICE (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The study tries to explore the relationship  between perceived organizational support  and psychological empowerment with job  performance. Further, it has also examined the  mediating effect of organizational justice in the  study. Sample for the study was collected from  educationist working in higher educational  institutions. Total 325 sample was used to  study the relationship among study variables.  Analysis of the study was done using IBM SPSS  and AMOS software version 22. The findings  of the study suggest that except one construct  (i.e. meaning) of psychological empowerment  rest all (i.e. competence, self-determination  and impact) have significant influence on job  performance. Whereas perceived organizational  support is found related with job performance.  The mediating effect of organizational justice is  found between POS and JP whereas it partially  mediates between PE and JP. The study is unique  which tries to understand the relationship of  study variables in context of higher educational  institutions in India.
Keywords: Psychological Empowerment; Perceived Organizational Support; Job Performance; organizational Justice; India